Mitochondrial GCN5L1 regulates glutaminase acetylation and hepatocellular carcinoma. Issue 5 (11th May 2022) - Zhang, Taotao; Cui, Yunlong; Wu, Yanjin; Meng, Jiahui; Han, Linmeng; Zhang, Jiaqi; Zhang, Chunyu; Yang, Chenxi; Chen, Lu; Bai, Xue; Zhang, Kai; Wu, Kaiyuan; et al.
Abstract: Background: Glutaminolysis is a critical metabolic process that promotes cancer cell proliferation, including hepatocellular carcinoma (HCC). Delineating the molecular control of glutaminolysis could identify novel targets to ameliorate this oncogenic metabolic pathway. Here, we evaluated the role of general control of amino acid synthesis 5 like 1 (GCN5L1), a regulator of mitochondrial protein acetylation, in modulating the acetylation and activity of glutaminase to regulate HCC development. Methods: Cell proliferation was determined by MTT, 2D and soft agar clone formation assays and orthotopic tumour assays in nude mice. GLS1/2 acetylation and activities were measured in cells and tumours to analyse the correlation with GCN5L1 expression and mTORC1 activation. Results: Hepatic GCN5L1 ablation in mice markedly increased diethylnitrosamine (DEN)‐induced HCC, and conversely, the transduction of mitochondrial‐restricted GCN5L1 protected wild‐type mice against HCC progression in response to DEN and carbon tetrachloride (CCl4 ) exposure. GCN5L1–depleted HepG2 hepatocytes enhanced tumour growth in athymic nude mice. Mechanistically, GCN5L1 depletion promoted cell proliferation through mTORC1 activation. Interestingly, liver–enriched glutaminase 2 (GLS2) appears to play a greater role than ubiquitous and canonical tumour–enriched glutaminase 1 (GLS1) in promoting murine HCC. Concurrently, GCN5L1 promotes acetylation and inactivation of both isoforms and increases enzyme oligomerisation. In human HCC tumours compared to adjacent tissue, there were variable levels of mTORC1 activation, GCN5L1 levels and glutaminase activity. Interestingly, the levels of GCN5L1 inversely correlated with mTORC1 activity and glutaminase activity in these tumours. Conclusions: Our study identified that glutaminase activity, rather than GLS1 or GLS2 expression, is the key factor in HCC development that activates mTORC1 and promotes HCC. In the Kaplan–Meier analysis of liver cancer, we found that HCC patients with high GCN5L1 expression survived longer than those with low GCN5L1 expression. Collectively, GCN5L1 functions as a tumour regulator by modulating glutaminase acetylation and activity in the development of HCC. Abstract : Mitochondrial GCN5L1 regulates proliferation and tumorigenesis in hepatocellular carcinoma (HCC) via glutamine metabolism. Deletion of general control of amino acid synthesis 5 like 1 (GCN5L1) enhances both glutaminase 1 (GLS1) and glutaminase 2 (GLS2) activities by altering acetylation and oligomerisation. Compound 968 inhibits GLS2 to suppress diethylnitrosamine (DEN)‐ and carbon tetrachloride (CCl4 )‐induced HCC development. Our study suggests that targeting glutaminase or mTORC1 activity could be a potential therapeutic treatment for HCC expressing lower levels of GCN5L1.